Nanogels as Novel Nanocarrier Systems for Efficient Delivery of CNS Therapeutics - Zhang, Yunhan; Zou, Zhulin; Liu, Shuang; Miao, Shengjie; Liu, Haiyan (Frontiers in Bioengineering and Biotechnology, 2022)
Nanogels have come out as a great potential drug delivery platform due to its prominently high colloidal stability, high drug loading, core-shell structure, good permeation property and can be responsive to environmental stimuli. Such nanoscopic drug carriers have more excellent abilities over conventional nanomaterials for permeating to brain parenchyma in vitro and in vivo. Nanogel-based system can be nanoengineered to bypass physiological barriers via non-invasive treatment, rendering it a most suitable platform for the management of neurological conditions such as neurodegenerative disorders, brain tumors, epilepsy and ischemic stroke, etc. Therapeutics of central nervous system (CNS) diseases have shown marked limited site-specific delivery of CNS by the poor access of various drugs into the brain, due to the presences of the blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCSFB). Hence, the availability of therapeutics delivery strategies is considered as one of the most major challenges facing the treatment of CNS diseases. The primary objective of this review is to elaborate the newer advances of nanogel for CNS drugs delivery, discuss the early preclinical success in the field of nanogel technology and highlight different insights on its potential neurotoxicity.